Loss reduction in distribution networks using new network reconfiguration algorithm - Kashem, M.A.; Moghavvemi, M.; Mohamed, A.; Jasmon, G.B. (1996)
Network reconfiguration is an operation task, and consists in the determination of the switching operations such to reach the minimum loss conditions of the distribution networks. In this paper, a general formulation of the network reconfiguration for loss minimization is given for the optimization of distribution loss reduction and a solution approach is presented. The solution employs a search over different radial configurations, created by considering branch exchange type switches. The solution algorithm for loss minimization has been developed based on the two stage solution methodology. The first stage of this solution algorithm finds a loop which gives the maximum loss reduction in the network. For this purpose a simple-to-use formula, called loop loss reduction formula, has been developed. To find a branch exchange, which results in the maximum loss reduction in the loop, the second stage applies a proposed technique called distance-center technique. Therefore, the solution algorithm of the proposed method can identify the most effective branch exchange operations for loss reduction, with a minimum computational efforts. The solution algorithm of the proposed method has been tested, with very promising results, on a 69-bus radial distribution system. Test results prove that, via proposed network reconfiguration for loss minimization, real power loss is reduced significantly, and that the voltage profile of the network is considerably improved. As compared to the established methods the proposed method eliminates the need to run numerous load flows.